2009
DOI: 10.1037/a0016812
|View full text |Cite
|
Sign up to set email alerts
|

Another breed of “service” animals: STARS study findings about pet ownership and recovery from serious mental illness.

Abstract: This study elucidates the role of pets in recovery processes among adults with serious mental illness. Data derive from interviews with 177 HMO members with serious mental illness (52.2% women, average age 48.8). Interviews and questionnaires addressed factors affecting recovery processes and included questions about pet ownership. Data were analyzed using a modified grounded theory method to identify the roles pets play in the recovery process. Primary themes indicate pets assist individuals in recovery from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 36 publications
6
69
0
Order By: Relevance
“…From Autistic Spectrum Disorders (Kern et al, 2011;O 'Haire, 2013) to severe mental illness (Barker & Dawson, 1998;Kamioka et al, 2014;Maujean et al, 2015;Wisdom et al, 2009), the literature increasingly indicates there is value in the facilitation of human-animal contact within interdisciplinary clinical practice. This therapeutic framework has resulted in the use of terms such as ''pet therapy'', ''animal-assisted therapy'' and ''animal-assisted activities'', referring to a reciprocal dynamic between humans and animals which addresses ''physical and/or emotional needs'' (Adams, 2010;Carmack, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…From Autistic Spectrum Disorders (Kern et al, 2011;O 'Haire, 2013) to severe mental illness (Barker & Dawson, 1998;Kamioka et al, 2014;Maujean et al, 2015;Wisdom et al, 2009), the literature increasingly indicates there is value in the facilitation of human-animal contact within interdisciplinary clinical practice. This therapeutic framework has resulted in the use of terms such as ''pet therapy'', ''animal-assisted therapy'' and ''animal-assisted activities'', referring to a reciprocal dynamic between humans and animals which addresses ''physical and/or emotional needs'' (Adams, 2010;Carmack, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…This had five different themes, with varying numbers of questions. The interview guide was based on previous research, primarily on the findings of Wisdom et al [10] .…”
Section: Interviewsmentioning
confidence: 99%
“…Wisdom et al also showed that the respondents' control of their pets and their relationships with their pets empowered them and increased their self-efficacy/self-worth, although in some cases, the responsibility combined with other stress factors became too much, sometimes leading to depression. The loss of an animal could also induce depression [10] .…”
mentioning
confidence: 99%
See 2 more Smart Citations